Survey of high‐dose‐rate prostate brachytherapy practice in Australia and New Zealand, 2010–2011. Issue 1 (29th July 2013) - van, Jane; Waterhouse, David; Bydder, Sean; Joseph, David; Ebert, Martin; Caswell, Nikki
Abstract Introduction A survey was designed to establish a baseline data set for the current routine practice of high‐dose‐rate prostate brachytherapy (HDR‐PB) in Australia and New Zealand. Existing treatment protocols and clinical implementations are not generally known. Methods The survey, for the 2010 and 2011 calendar years, collected data including number of patients treated; equipment used; imaging modalities; applicator verification and correction methods; dose prescriptions and normal tissue dose constraints. The number of HDR‐PB patients treated was compared with the most recently published prostate cancer incidence data in Australia and in New Zealand. Total biologically equivalent doses in 2.0 Gy fractions (EQD2) were calculated for each prescription regime reported. Results There were reductions, of 25–60%, in patients treated with HDR‐PB from 2010 to 2011 in four departments. Prostate cancer patients are two to six times more likely to be prescribed HDR‐PB in Western Australia than elsewhere in the region. There were 12 different treatment prescriptions, with EQD2 doses ranging from 73.5 to 97.6 Gy, among the 18 reported by survey respondents. Normal tissue definition methodology and dose constraints varied, and 13 of 15 departments reported that no particular published external guidelines were followed in full. Conclusion The high survey response rate, 15 of 17 departments, has provided a representative baseline data set of contemporary HDR‐PB practice in Australia and New Zealand that may assist government and professional bodies, such as the Australasian Brachytherapy Group, in formulating recommendations, setting standards and future planning.